Pengaruh Stimuli Lingkungan dan Faktor Sosial Terhadap Kecenderungan Shopaholic Emosi Positif Sebagai Variabel Mediasi pada Konsumen Suzuya Mall di Banda Aceh - Badaruddin Badaruddin (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2017)
This study was done to examine the effect from environment stimulus and social factor toward impulse buying and positive emotion as mediating variable (study on consumers at Suzuya in Banda Aceh city), the respondents of this study is the consumers who shops at Suzuya in Banda Aceh city with respondent for 150 people. With respondent 150 people, sample determination is using purposive sampling. Model analysis in this study is using path analysis. Based on the result of path analysis found that environment stimulus have influence on positive emotion, social factor have influence on positive emotion, environment stimulus have influence on impulse buying, social factor have influence on impulse buying, positive emotion have influence on impulse buying, there are indirect effects of environment stimulus and impulse buying mediated by positive emotion, and there are direct and indirect effects of social factor toward impulse buying mediated by positive emotion.